2003
DOI: 10.1029/2001jd001562
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol time‐of‐flight mass spectrometry during the Atlanta Supersite Experiment: 1. Measurements

Abstract: [1] In August 1999 an intensive field campaign was conducted in Atlanta, Georgia, focusing on the characterization of urban particulate matter. During the study an aerosol time-of-flight mass spectrometer (ATOFMS) was used to measure continuously the aerodynamic size and chemical composition of individual particles in the fine fraction (0.2-2.5 mm) of the atmospheric aerosol. The inorganic and organic components of the particles were analyzed using laser desorption ionization time-of-flight mass spectrometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
81
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 53 publications
15
81
1
Order By: Relevance
“…Fig. 4 Temporal variations in EC and BC Particles are considered "aged" when a high percentage of secondary species is formed (Liu et al 2003;Yang et al 2011); aged carbonaceous aerosols become more internally mixed in, e.g., a shell-core structure with other species. For example, Yang et al (2011) observed that most submicron carbonaceous aerosols were internally mixed with ammonium nitrate and secondary organic compounds during the HH episode of Shanghai winter.…”
Section: Exploratory Probe Of the Bc/ec Divergence In The Hh Periodmentioning
confidence: 99%
“…Fig. 4 Temporal variations in EC and BC Particles are considered "aged" when a high percentage of secondary species is formed (Liu et al 2003;Yang et al 2011); aged carbonaceous aerosols become more internally mixed in, e.g., a shell-core structure with other species. For example, Yang et al (2011) observed that most submicron carbonaceous aerosols were internally mixed with ammonium nitrate and secondary organic compounds during the HH episode of Shanghai winter.…”
Section: Exploratory Probe Of the Bc/ec Divergence In The Hh Periodmentioning
confidence: 99%
“…Particles containing amines were identified by the mass spectrometric marker of alkylamines at m/z þ86 [NCH 2 (C 2 H 5 ) 2 þ ] [17] with a threshold of an absolute peak area larger than 100 and a relative peak area greater than 0.05. Other aerosol time-of-flight mass spectrometry markers used were m/z þ18 [NH 4 þ ] (absolute peak area greater than 30), [49] À97 [HSO 4 À ] (absolute peak area greater than 100) [49] and À195 [H(HSO 4 ) 2 À ] (absolute peak area greater than 30), indicative of ammonium salts, sulfate compounds and particle acidity index [44] respectively. Particles were clustered into six major types using the ART-2a (adaptive resonance theory) [50] method with a vigilance factor of 0.7, a learning rate of 0.05 and 20 iterations based on the similarities of mass-to-charge ratio and peak intensity.…”
Section: Methodsmentioning
confidence: 99%
“…The peak lists were subsequently imported into MATLAB 7.1 (The Mathworks Inc.) and analyzed using YAADA 2.1 (www.yaada.org), a MATLABbased software toolkit used for processing the single-particle mass spectral data. Peak identification described in this paper corresponds to the most probable assignments for each specific mass-to-charge ratio (m/z), and more details can be found in the published work by Liu et al (2003) and Murphy and Thomson (1997a, b).…”
Section: Single Particle Data Analysismentioning
confidence: 99%